A Case of Hyalinizing Clear Cell Carcinoma, So-Called Clear Cell Carcinoma, Not Otherwise Specified, of the Minor Salivary Glands of the Buccal Mucosa. (27th October 2015) - Yamanishi, Takahiro; Kutsuma, Kiwako; Masuyama, Keisuke
Abstract : Hyalinizing clear cell carcinoma (HCCC), so-called clear cell carcinoma, not otherwise specified (CCC (NOS)), of the salivary glands is a rare and low-grade malignant tumor. We report a case of HCCC so-called CCC (NOS) (referred to as HCCC) of the minor salivary gland of the buccal mucosa. A 52-year-old woman had presented with a gradually growing and indolent mass in the right buccal mucosa for about two years. The first biopsy histopathologically suggested the possibility of malignancy derived from the minor salivary glands. A month later, she visited our hospital. The tumor measured approximately 1.5 cm in diameter and was elastic hard, smooth, and well movable. Image examinations demonstrated internal homogeneity of the lesion, which had a smooth margin, in the right buccal mucosa. Complete tumor resection followed by covering with a polyglycolic acid sheet and fibrin glue spray was performed without surgical flap reconstruction. Histopathological findings revealed proliferating tumor cells with clear cytoplasm surrounded by hyalinizing stroma in the submucosal minor salivary glands. Immunohistochemical stains revealed these tumor cells to be positive for epithelial cell markers but negative for myoepithelial ones. These findings confirmed the diagnosis of HCCC. Good wound healing and no evidence of local recurrence and metastasis have been shown since surgery.